1 Detection of calcification in atherosclerotic plaques using optical imaging. (26th March 2018) - Sim, Alisia M; Rashdan, Nabil A; Lin, Cui; Nudelman, Fabio; Dweck, Marc; MacRae, Vicky E; Hulme, Alison N
Abstract : Introduction: PET imaging, using the bone tracer Na 18 F, allows the non-invasive location of atherosclerotic plaques that are at risk of rupture. However, the spatial resolution of PET is only 4–5 mm, limiting the mechanistic information this technique can provide. Methods: In this project, the use of fluorescence and Raman imaging to elucidate the mechanism of microcalcification within atherosclerotic plaques has been investigated. Results and conclusion: A fluorescent probe to specifically detect calcium has been synthesised: it has been shown to: selectively bind to hydroxyapatite (HAP), permit visualisation and quantification of HAP in both vascular and bone cell models, effectively stain cultured aortic sections and whole mouse aorta for OPT imaging. It is believed that the biosynthetic pathway to HAP passes through a series of transitional states; each of these has different structural characteristics which can be studied using Raman spectroscopy. In particular, HAP has a strong characteristic Raman peak at 960 cm -1 . An increase in HAP concentration has been detected by Raman in both calcified cell models and aortic sections. Building on these preliminary data, fluorescence and Raman imaging of both healthy and atherosclerotic tissue are planned.